2021
DOI: 10.3389/fimmu.2021.646523
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Pan-Cancer Analysis Identifies TREM2 as an Immunological and Prognostic Biomarker

Abstract: Triggering receptor expressed on myeloid cells-2 (TREM2) is a transmembrane receptor of the immunoglobulin superfamily and a crucial signaling hub for multiple pathological pathways that mediate immunity. Although increasing evidence supports a vital role for TREM2 in tumorigenesis of some cancers, no systematic pan-cancer analysis of TREM2 is available. Thus, we aimed to explore the prognostic value, and investigate the potential immunological functions, of TREM2 across 33 cancer types. Based on datasets from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 41 publications
3
66
0
Order By: Relevance
“…The ssGSEA using R package "GSVA" was applied for the quantification of 11 immune signatures, including MHC class I, APC co inhibition, chemokine receptors (CCR), APC co stimulation, T cell co-inhibition, check-point, T cell co-stimulation, inflammationpromoting, parainflammation, Type I IFN response, and Type II IFN response [20]. The R packages "reshape2" and "RColorBrewer" were applied to perform a co-expression analysis of MICALL2 and immunoregulatory genes associated with major histocompatibility complex (MHC), immunosuppression, immune activation, chemokines, and chemokine receptors [21].…”
Section: Micall2 Expression and Immunitymentioning
confidence: 99%
“…The ssGSEA using R package "GSVA" was applied for the quantification of 11 immune signatures, including MHC class I, APC co inhibition, chemokine receptors (CCR), APC co stimulation, T cell co-inhibition, check-point, T cell co-stimulation, inflammationpromoting, parainflammation, Type I IFN response, and Type II IFN response [20]. The R packages "reshape2" and "RColorBrewer" were applied to perform a co-expression analysis of MICALL2 and immunoregulatory genes associated with major histocompatibility complex (MHC), immunosuppression, immune activation, chemokines, and chemokine receptors [21].…”
Section: Micall2 Expression and Immunitymentioning
confidence: 99%
“…In addition, Xiong et al reanalyzed a publicly available scRNA-seq dataset of melanoma samples of patients subjected to ICIs and identified a subpopulation of macrophages overexpressing TREM2 that were overrepresented in the non-responding tumors, and this subpopulation of macrophages might contribute to the resistance of ICIs (89). In order to systematically explore the potential immunological functions and the potential prognostic value of TREM2 across 33 cancer types, Cheng et al conducted a pancancer analysis based on datasets from The Cancer Genome Atlas, the Cancer Cell Line Encyclopedia, Genotype Tissue-Expression, cBioPortal and Human Protein Atlas, they used the ESTIMATE algorithm to calculate the immune scores across the 33 types of cancers, their results showed that the expression level of TREM2 was significantly positively correlated with immune scores in diffuse large B-cell lymphoma, acute myeloid leukemia and thymoma, and the levels of immune cell infiltration were significantly correlated with TREM2 expression in most types of malignancies (90), this indicated that TREM2 could function as a prognostic marker in various cancers because of its especial role in tumorigenesis and tumor immunity. Lately, Lee et al demonstrated for the first time that precursor natural killer (pNK) cells expressed TREM2, compared with wild type mice, the population of pNK cells and the expression levels of NK cell-activating receptors and NK cell-associated genes were all increased in TREM2-overexpressing transgenic mice, on the contrary, the inhibition of TREM2 signaling pathway by TREM2-immunoglobulin or PI3K inhibitor impacted the expression of NK cell receptor repertoire and downregulated the expression levels of NK cell-associated genes, thus significantly impaired the differentiation of NK cells, the results of this study collectively suggested again that TREM2 might act as a novel candidate for cancer immunotherapy (91).…”
Section: Application Of Trem2 In Cancer Immunotherapymentioning
confidence: 99%
“…To widen the potential therapy options for malignancies, a better knowledge of carcinogenesis and tumor progression through the identification of oncogenes is crucial. Large-scale and multi-omics cancer datasets, such as The Cancer Genome Atlas (TCGA) ( ICGC/TCGA Pan-Cancer Analysis of Whole Genomes Consortium, 2020 ; Ye et al, 2021 ; Lv et al, 2021 ; Cheng et al, 2021 ; Cui et al, 2020 ), have made pan-cancer analysis possible in the last decade.…”
Section: Introductionmentioning
confidence: 99%